HUBUNGAN ANTARA KADAR LIPID DARAH DENGAN DERAJAT HERNIASI DISKUS INTERVERTEBRALIS - Elsa Ana Purika,* Susi Aulina,* Audry Devisanty Wuysang,* Andi Alfian Zainuddin** (NEURONA, 2019)
INTRODUCTION INTERVERTEBRAL DISC HERNIATION IDH IS ONE OF THE COMMON CAUSES OF LOW BACK PAIN LBP HIGH LEVEL OF BLOOD LIPIDS IS A RISK FACTOR FOR ATHEROSCLEROSIS AND RESPONSIBLE AS THE CAUSE OF DECREASED BLOOD SUPPLY TO THE INTERVERTEBRAL DISCS WHICH BASICALLY HAS MINIMAL VASCULARIZATION THUS IT IS ESTIMATED THAT THERE IS A RELATIONSHIP BETWEEN BLOOD LIPID LEVELS AND IDH